The impact of exogenous and endogenous factors on external knowledge sourcing for innovation: The dual effects of the external environment - Yoo, So-jin; Sawyerr, O.; Tan, W. (Elsevier, 2015)
In this study we postulate that a firm's external knowledge sourcing decision is determined by factors that are exogenous and endogenous to the firm and that exogenous factors moderate the effect of endogenous factors on a firm's external knowledge sourcing decision. Exogenous factors of the external environment such as market and technology turbulence and competitive intensity are assumed to induce a firm to source knowledge externally for innovation, whereas endogenous factors such as ambiguity avoidance, organizational inertia, and low absorptive capacity may inhibit external knowledge sourcing. In this study, particularly, we examine both the direct effects of exogenous and endogenous factors as well as the moderating effect of the exogenous factors on firm-specific characteristics on a firm's external knowledge sourcing decision. We postulate that on the one hand, environmental factors may prompt firms to source knowledge externally; however, they may also prevent firms from engaging in external knowledge sourcing by moderating specific organizational attributes endogenous to the firm, thus producing a dual effect. We present research findings from a sample of 127 innovative Korean SMEs to support the existence of direct effects of environmental and firm-specific factors as well as the moderating effects of the external environment on firm-specific factors on a firm's external knowledge sourcing decision with customers, suppliers & distributors and other firms. We discuss the findings and provide directions for future research